Digital Electronic Early Warning Scores for Early Detection of Patient Deterioration and Nursing Response: A Systematic Literature Review - Nawawi Nawawi; Wastu Adi Mulyono (GLOBAL HEALTH SCIENCE GROUP, 2026)
Early recognition of patient deterioration and prompt clinical intervention are essential components of quality healthcare and patient safety. Digital-based Electronic Early Warning Score (E-EWS) systems have been developed to facilitate the early identification of clinical deterioration; however, evidence regarding their effectiveness remains inconclusive. This systematic review aimed to examine the role of digital E-EWS systems in enhancing the early detection of patient deterioration and improving nursing responses across various clinical settings. A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Relevant studies published between 2015 and 2025 were retrieved from PubMed, PMC, Scopus, Google Scholar, Springer, and MDPI databases. The search strategy employed the following keywords: (“Electronic Early Warning Score” OR “digital early warning system”) AND (“patient deterioration” OR “early detection”) AND (“nursing response” OR “rapid response” OR “escalation”) AND (inpatient OR hospital OR ward). A total of 133 articles were initially identified, and after screening based on PICOS criteria, nine studies met the eligibility criteria and were included in the final analysis. The selected studies evaluated the impact of E-EWS implementation on early detection of patient deterioration, clinical processes, nursing responses, and patient outcomes. The findings demonstrated that digital E-EWS systems improved the accuracy and completeness of vital sign documentation, enabled earlier identification of high-risk patients, and strengthened clinical escalation through automated alerts and standardized response recommendations. Improvements in nursing practice were also observed, including increased monitoring frequency, enhanced interprofessional communication, and more timely activation of Rapid Response Teams (RRT). Nevertheless, evidence regarding major clinical outcomes, such as mortality, cardiac arrest, and unplanned intensive care unit (ICU) admissions, remained inconsistent across studies. Variability in study design, differences in E-EWS platforms, and limited reporting of nursing interventions posed challenges to establishing definitive conclusions. Overall, digital E-EWS systems demonstrate considerable potential to improve patient safety and support the quality of nursing care in contemporary healthcare settings.